Frequency distribution of pre-messenger RNA sequences in polyadenylated and non-polyadenylated nuclear RNA from Friend cells. - Balmain, A (1980)
Hybridisation of cDNA probes for abundant and rare polysomal polyadenylated RNAs with polyadenylated and non-polyadenylated nuclear RNA from Friend cells indicated that the abundant polysomal polyadenylated RNA sequences were present at a higher concentration in the nucleus than rare polysomal sequences, but at a reduced range of concentrations. The ratio of the concentrations of abundant and rare sequences was about 3 in non-polyadenylated nuclear RNA, 9 in polyadenylated nuclear RNA and 13 in polysomal polyadenylated RNA. This suggests that polyadenylation may play a role in the quantitative selection of sequences for transport to the cytoplasm. Polyadenylation cannot be the only signal for transport, since a highly complex population of nucleus-confined polyadenylated molecules exists, each of which is present on average at less than one copy per cell.